Asymmetric impacts of El Niño and La Niña on the Pacific–North American teleconnection pattern: the role of subtropical jet stream. (8th November 2021) - Wang, Ya; Hu, Kaiming; Huang, Gang; Tao, Weichen
Abstract: The asymmetric impacts of El Niño and La Niña on the Pacific–North American teleconnection pattern in boreal winter have important implications for the surface air temperature and precipitation anomalies in North America. Previous studies have shown that the varying tropical convective heating contributes to the zonal shift of the teleconnection pattern during different El Niño/Southern Oscillation phases. In this study, using reanalysis, atmospheric general circulation model (AGCM) simulations, and a linear baroclinic model, we further present that the discrepancy of the subtropical jet stream (STJ) during El Niño and La Niña also contributes to the asymmetry. The atmospheric anomalies readily extract kinetic energy and effectively develop at the exit of the STJ. During El Niño (La Niña) years, as the central-eastern tropical Pacific warms up (cools down), the meridional temperature gradient in central subtropical Pacific increases (decreases), leading to the eastward (westward) shift of the STJ. The movement of the STJ leads to the shift of the location where disturbance develops most efficiently, ultimately contributing to the asymmetry of the teleconnection pattern.